Colloidal Stability of Aqueous Suspensions of Polymer-Coated Iron Oxide Nanorods: Implications for Biomedical Applications - Marins, J. A; Montagnon, T; Ezzaier, H; Hurel, Ch; Sandre, O; Baltrunas, D; Mazeika, K; Petrov, A; Kuzhir, P (ACS applied nano materials, 2018)
Iron oxide nanorods are considered to be very promising platforms for biomedical applications, such as magnetic hyperthermia, magnetic resonance imaging, or immunoassays based on magnetooptical effects. However, their efficient colloidal stabilization is challenging, and colloidal aggregation could lead to the total loss of their performance. This work is focused on the synthesis and colloidal stabilization of iron oxide nanorods of an average length and diameter, L × d = 31 × 6 nm, synthesized by the hydrolysis of iron(III) salt, followed by reduction of the obtained akaganeite to iron oxide in a microwave reactor. Synthesized nanorods exhibited a weak ferrimagnetic behavior with remnant magnetization M R ∼ 3 emu/g and saturation magnetization M S ∼ 13 emu/g. The nanorods were dispersed in water after adsorption on their surface of three different polymers: linear bisphosphonate–poly(ethylene glycol) (PEG) molecules (denoted as OPT), polymethacrylate backbone/PEG side chains comb polymer (denoted as PCP; with PEG brushes both extended toward the solvent and having molecular weight M w ∼ 3000 g/mol), and polyacrylic sodium salt (PAA; M w ∼ 15000 g/mol). Experiments and theoretical evaluation of the interaction potential show that increasing the polymer grafting density on the nanorod surface as well as decreasing the concentration of a nonadsorbed polymer improve the nanorod colloidal stability. The best stability is obtained on an optimal range of weight ratio of the added polymer to the nanorods between 0.5 and 1.6 mg/mg. A higher grafting density reached with a OPT polymer with a bisphosphonate terminal group (2–4 nm–2) allows much better stability than using multiple adsorption with PCP (0.2–0.4 nm–2) or PAA. Even though the nanorods are still subject to some aggregation (effective hydrodynamic diameter ∼60 nm, compared to their TEM size of L × d = 31 × 6 nm), significant progress toward understanding their colloidal stability was achieved.